Journalists’ professional identity: new challenges to an old quest - Fidalgo, Joaquim (2008)
The efforts made by journalists, in different countries and within different social and historical contexts, to have their ‘craft’ or ‘occupation’ recognized as a true ‘profession’, have always been somehow contradictory and ambiguous. The appeal of professionalism still divides opinions inside the professional group itself, with some voices claiming for a more demanding set of conditions to enter and work in this activity (for example, a University degree and stronger accountability mechanisms), and other voices insisting that it must be an ‘open’ job in order to guarantee the universal right to freedom of expression. Actually, the journalists’ professional group seems very often to claim the benefits and privileges of being legally treated as a ‘profession’, but doesn’t look equally demanding when it comes to the responsibilities and duties implied by such a status. The activity of gathering and disseminating news and information in the public sphere – which was some kind of a monopoly in the journalists’ hands – has, in the meantime, become accessible to almost everyone, everywhere, thanks to the Internet and the digital technologies. Within this context, new questions seem to challenge the very definition of a journalist or, at least, the core elements that should differentiate his/her professional identity from a multiplicity of other practitioners in the open field of public communication. And that, as we try to discuss in this paper, could bring us back to a kind of reviewed professionalism.